Climate Change Agriculture and Food Security Learning Platform 5: cross-cutting platform on gender and climate-smart agriculture - Huygens, Sophia; Nyasimi, Mary (International Center for Tropical Agriculture, 2017)
Presented by Sophia Huygens and Mary Nyasimi (CCAFS / CIAT), as part of the Capacity Development Workshop hosted by the CGIAR Collaborative Platform for Gender Research, Amsterdam, 7-8 December 2017